The Maximum Tax on Earned Income–A Graphical Illustration. - Lake, Robert C. (The Accounting Review, 1976)
Abstract The article presents a simple graphical illustration for the maximum tax on earned income. Internal Revenue Code, section 1348 stipulates that the maximum rate of taxation of "earned income" shall be 50 percent. In spite of the relative simplicity of this concept, students often experience difficulty understanding computations required to accomplish the objectives of the section. Standards texts, though yielding descriptions which are clear and accurate, are not particularly helpful to the student attempting to conceptualize the procedures. A simple graphical presentation, can make obvious the logic underlying computations. Of course, the contribution of this graphical approach is that the significance of the third step in computations just described becomes apparent. Only in this manner is it possible to easily compute the tax on the "unearned" portion of taxable income, since it is desired to tax this income at the same marginal rates which would have been applied had section 1348 not been invoked.